ECONOMIC VALUE ASSESMENT OF THE SUMATRAN TIGER: AN APPLICATION OF CONTINGENT VALUATION METHOD IN GUNUNG LEUSER NATIONAL PARK, INDONESIA - Thi Thu Ha, Tran; Triana, Novelia (Journal of Forestry Science and Technology, 2020)
The Contingent Valuation Method (CVM) study is the way to get to know the economic value of species by their existence. It is also considering their presence for the future generation since they are non-use value. In reality, it is hard to identify their exact value, but from this kind of research, it would provide the economic consideration for conservation management. The objective of the research is to assess economic value of Sumatran tiger by evaluating the Willingness to Pay (WTP) of the people and assessing the factors influencing WTP of Sumatran Tiger conservation program. The scenario of the WTP assumes the consideration of respondent to contribute to the conservation program of Sumatran Tiger and mitigating the conflict on local people. The value of WTP on Sumatran tiger conservation is 67,512 IDR or equal to 4.82 USD. The results show that 61.33% of people are willing to pay, but 38.67% of respondents are not willing to pay for tiger conservation. The emperical data also shows that there are five factors are affecting significantly to people’s decision through the bid level for the Sumatran Tiger WTP including Household size, Threatened, Believe, City1, and City2. As the people have desire for willing to pay for conservation Sumatran Tiger, it might be the potential funding raise as a strategy. Community-based conservation would be the mitigation strategy for improving the participatory conflict management.